Evaluación de los procesos que controlan la progradación de la barrera costera de las playas del Parque Nacional Natural Tayrona (2020)
Most of beaches in the Colombian Caribbean have a very marked negative sedimentary budget that results in their erosion, although this trend is predominant on the Colombian Caribbean coast. The PNN-Tayrona shows an opposite behavior with a sedimentary balance positive that results in accretion and stability in many of its beaches. Due to the lack of information in this regard and the ignorance of the causes that favor the occurrence of these conditions in that protected area, the objective of this investigation is to evaluate the controlling processes of the progradation of the coastal barrier of the beaches of the PNN-Tayrona, Colombia. For this, it was necessary to collect satellite and drone images between the years 2012-2018, as well as the collection of Coordinates with a DGPS for its subsequent geoprocessing with DSAS and other computer tools. From the above, it was found that the beaches with the highest positive sedimentary balance are Arenilla and Arrecifes. The beaches with the highest negative sedimentary balance were Gumarra and Príncipe San Felipe. Particularly the Piscina beach, despite being located in front of a coral reef and to the west of the beaches that stand out for their accretion in recent years, this one presents erosion. The morphodynamic state that occurs mostly on the beaches of the study area is dissipative and the hydrographic basin that has the greatest sedimentary contribution on the beaches is that of the Piedra River.